Interactive effect of score levels on students' performance in social studies - Omotayo Olabo Obielodan; Amos Ochayi Onojah; Adenike Aderogba Onojah; Ebenezer Sanya Ibironke; Esther Oluwafunmilayo Alabi (Himpunan Pengembang Kurikulum Indonesia, 2022)
Technological developments in the modern era may help teachers learn about a collaborative learning environment. Technology can motivate students and allow them to be engaged on a completely different level than they have ever before. It also increases student academic experience. This study examined the interactive effect of score levels on students' social studies performance. The data testing in this study was carried out with the ANOVA test on 29 junior secondary schools. This research was conducted by examining the interactive effect of the audio-visual score level on students' academic achievement in social studies subjects. The study employs an experimental research method of these 21 junior secondary school students sampled to test the audio-visual. The findings established that audio-visual improves students' academic performance in social studies. There was no significant interactive effect of score levels on students' performance in social studies. The study concluded that audio-visual improves students' social studies performance irrespective of their score levels. It was thus recommended that social studies teachers be encouraged to use audio-visual aids as it gives more meaningful learning to students. Besides, the Government should employ qualified and well-skilled teachers to teach the course, and the curriculum planner must be careful in designing material to teach social studies.